IMPROVING THE STUDENTSâ READING COMPREHENSION THROUGH âTELLSâ STRATEGY AT THE FIRST YEAR STUDENTS OF SMA MUHAMMADIYAH 9 PERUMNAS MAKASSAR - Ilmiah, Ilmiah; Mustakim, Abd. (Lembaga Perpustakaan Unismuh Makassar, 2013)
This research aimed to improve studentsâ reading comprehension by using strategy of tittle, examine, look, look and setting. This research used Classroom Action Research (CAR) by implementing two cycles (cycle 1 and 2). This research tried to find out the studentsâ achievement in literal comprehension through TELLS Strategy and the studentsâ achievement in interpretive comprehension through TELLS Strategy. Then the researcher found the results based on the goals of the research, those were the studentsâ improvement in literal reading comprehension was 67.75% from 51.31%, as well as the studentsâ improvement in interpretative reading comprehension 67.10% from 51.31%. It was reached by the implementation of TELLS Strategy in the classroom.Keywords: Reading, TELLS Strategy, CAR, Literal, Interpretative.Penelitian ini bertujuan untuk meningkatkan pemahaman membaca siswa dengan menggunakan strategi tittle, examine, look, look and setting (TELLS). Penelitian ini menggunakan Penelitian Tindakan Kelas (PTK) dengan menerapkan dua siklus (siklus 1 dan 2). Penelitian ini mencoba untuk mengetahui prestasi dalam pemahaman literal melalui TELLS Strategi dan prestasi siswa dalam pemahaman interpretatif melalui TELLS Strategi. Kemudian peneliti menemukan hasil berdasarkan tujuan penelitian, mereka adalah peningkatan pemahaman literal membaca siswa adalah 67,75% dari 51,31%, serta peningkatan pemahaman membaca interpretatif siswa 67,10% dari 51,31%. Hal itu dicapai dengan penerapan TELLS Strategi di dalam kelas.Kata Kunci: Reading, TELLS Strategi, CAR, Literal, Interpretative.